2008
DOI: 10.1097/sla.0b013e318185a9ad
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma and Platelet to Red Blood Cell Ratios Improves Outcome in 466 Massively Transfused Civilian Trauma Patients

Abstract: Current transfusion practices and survival rates of MT patients vary widely among trauma centers. Conventional MT guidelines may underestimate the optimal plasma and platelet to RBC ratios. Survival in civilian MT patients is associated with increased plasma and platelet ratios. Massive transfusion practice guidelines should aim for a 1:1:1 ratio of plasma:platelets:RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
601
1
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 996 publications
(647 citation statements)
references
References 94 publications
18
601
1
14
Order By: Relevance
“…A subsequent study from 16 US trauma centres between 2005 and 2006 reported similar findings, with retrospective analysis showing improved survival with ratios of FFP:PRBC greater than 1:2 [19]. These results, and the biologically plausible concept of treating haemorrhage with component ratios approaching those of whole blood, have led to the development of guidelines recommending early empirical use of FFP in traumatic bleeding [20].…”
Section: Haemostatic Resuscitationsupporting
confidence: 52%
“…A subsequent study from 16 US trauma centres between 2005 and 2006 reported similar findings, with retrospective analysis showing improved survival with ratios of FFP:PRBC greater than 1:2 [19]. These results, and the biologically plausible concept of treating haemorrhage with component ratios approaching those of whole blood, have led to the development of guidelines recommending early empirical use of FFP in traumatic bleeding [20].…”
Section: Haemostatic Resuscitationsupporting
confidence: 52%
“…The Trauma Outcomes Group collected data from 466 massive transfusion patients from 16 level 1 centers from 2005 to 2006. 35 These data documented the wide variability in transfusion practice and outcomes across the United States. This study demonstrated that outcomes were improved with a more balanced ratio of at least 1:1:2.…”
mentioning
confidence: 99%
“…In severe ongoing hemorrhage survival is improved when RBC and plasma are used in 1:1 basis 28 . Timely transfusion of platelets at 1:1:1 rates is even more important to prevent coagulopathy 29 .…”
Section: Resultsmentioning
confidence: 99%